War and inflation in the United States from the revolution to the first Iraq War - Hugh Rockoff (Rutgers University, Department of Economics, 2015)
The institutional arrangements governing the creation of money in the United States have changed dramatically since the Revolution. Yet beneath the surface the story of wartime money creation has remained much the same. During wars against minor powers, the government was able to fund the war by borrowing and levying taxes. In major wars, however, there came a point when further increases in taxes could not be undertaken for administrative or political reasons, and further increases in borrowing could not be undertaken except at higher interest rates; rates that exceeded what was considered fair based on prewar norms. At those moments governments turned to the printing press. The result was substantial inflation.
Keywords: 330